Systematics of Baccharis (Asteraceae: Astereae) - Heiden, Gustavo (2014)
A comprehensive phylogenetic hypothesis for the predominantly Neotropical American genus Baccharis is necessary to test its monophyly and clarify the infrageneric relationships within the genus. Given its great morphological diversity and wide geographic distribution, phylogenetic studies based on molecular data to test the monophyly of the genus and investigate the relationships of its infrageneric groups are here proposed, allowing the recognition and taxonomic revision of smaller and monophyletic taxa. Therefore, a phylogenetic hypothesis for Baccharis is provided based on 248 species sampled, four molecular regions (ETS, ITS, trnH-psbA, trnL-F) and Bayesian analyses. The results confirm subtribe Baccharidinae as a monogeneric group, and support a wide definition of Baccharis s.l., monophyletic and including all genera that were previously segregated from it. Comprehensive lists of infrageneric taxa and taxa accepted at species level were compiled to move towards a phylogeny-based infrageneric classification of Baccharis. Seven main lineages were recovered, treated here at subgeneric level, and in this process all subgenera recognized before had to be recircumscribed to constitute monophyletic taxa. Four subgenera roughly match previous subgeneric concepts, while two subgenera are synonyms. Two earlier segregated genera and two formerly existing sections are moved to the subgeneric rank. The survey of names published in the ranks of sections and series accounted 68 sections and 13 series; four new sections are described and three new statuses at the rank of section are proposed to accommodate taxa not corresponding to any previously described section, while 22 sections were considered synonyms. This procedure allowed the recognition of 47 sections, though this number is supposed to decrease after future studies are accomplished with a larger sampling. The names accepted at species level totalize 433 taxa that were here assigned to the most inclusive infrageneric category possible in the light of the data currently available. Baccharis subgen. Tarchonanthoides Heering, a group restricted to the southeastern South American grasslands and savannas, was chosen as a good target to first tackle for a taxonomic revision, due its small size, restricted area of occurrence when compared to the remaining subgenera, and morphological distinctiveness. This is the first attempt to provide a taxonomic revision of a subgenus of Baccharis according to a phylogenetic framework, and under no geographic constraint. The recircumscription of Baccharis subgen. Tarchonanthoides involves the synonymization of Lanugothamnus, and the exclusion of one section in order to keep the subgenus monophyletic. Other taxonomic and nomenclatural actions necessary are designation of lectotypes, a new status and new combinations, new synonymizations and clarification of the species concepts formerly misapplied to some names. Two recircumscribed sections and 13 species are accepted within the taxonomically revised B. subgen. Tarchonanthoides, which diversified mainly in open vegetations from southeastern South America in Brazil, Paraguay, Uruguay and Argentina. General morphological descriptions of the infrageneric taxa are provided, as well as a taxonomic key, descriptions, data on etymology, distribution and habitats, phenology, conservation status, etnobotany and vernacular names, and a list of specimens examined, line drawings, pictures and maps of distribution for all accepted species within this subgenus. Alongside the main goals, exploratory fieldwork and study of herbaria specimens allowed the description of eight new species: B. dichotoma, B. hemiptera, B. magnifica, B. napaea, B. nebularis, B. obdeltata, B. simplex and B. umbellata